(untitled) (Don Bosco Institute of Technology Delhi Journal of Research, 2024)
Purpose- The paper aims to provide a conceptual review of mergers and acquisitions (M&A) in the Indian banking sector, highlighting the evolution, strategic motivations, legal aspects, and ethical considerations of M&A activities. Design/methodology/approach- The research methodology involves a qualitative literature review of scholarly articles, books, and relevant academic sources. The review focuses on identifying key themes related to the motivations, processes, and outcomes of M&A in the banking sector. Findings- The study finds that M&A activities in the Indian banking sector are primarily driven by the need for synergy, improved managerial efficiency, growth, and technological advancements. Synergies achieved through M&A can enhance revenue, performance, and cost efficiency. The paper also highlights the importance of ethical considerations and cultural integration during M&A processes to ensure smooth transitions and maintain organizational stability. Research limitations/implications- This study is based on existing literature, and empirical validation through case studies or primary data could further substantiate the findings. Future research could explore the long-term impact of M&A on financial performance and stakeholder value in the Indian banking sector. Practical implications- The findings provide valuable insights for banking sector stakeholders, by elucidating the strategic motivations and critical factors influencing successful M&A transactions. Originality/value- The paper offers a detailed conceptual framework for understanding the dynamics of M&A in the Indian banking sector, contributing to the existing body of knowledge and guiding future research and practice in this field.